1985
DOI: 10.1254/jjp.38.347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gomisin A on Liver Functions in Hepatotoxic Chemicals-Treated Rats

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…Gomisin A is the most active component among these lignans (20). It was reported that gomisin A prevents some experimental acute liver injuries (8). However, the nature of the protective mechanisms involved remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gomisin A is the most active component among these lignans (20). It was reported that gomisin A prevents some experimental acute liver injuries (8). However, the nature of the protective mechanisms involved remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Gomisin A improves histologically the hepatic cell degeneration, necrosis, and resultant inflammatory reactions in experimental liver injury models induced by carbon tetrachloride, GalN, α-naphthyl isothiocyanate, and orotonic acid (8). In addition, gomisin A has been reported to be effective in improving immunologicallyinduced acute hepatic failure (9) as well as in stimulating liver regeneration after a partial hepatectomy (10).…”
Section: Introductionmentioning
confidence: 99%
“…Gomisin A suppressed the appear ance of the lesions in the early stages after 3'-MeDAB. It is possible that gomisin A de creases the reversible fractions by improving of hepatic functions (6)(7)(8). Other molecular mechanisms of inhibition by gomisin A of tumor promotion should be considered and in vestigations on these mechanisms are in prog ress in our laboratory.…”
Section: Discussionmentioning
confidence: 97%
“…10 ) We investigated the effects of 1 on ICG clearance, and conclude that 1 accelerated the disappearance of plasma ICG in normal rats. This finding suggests that the process for hepatoprotection of 1 against both injuries may be related to an enhancement of the liver function, especially for hepatic transport.…”
Section: Mechanism For Antihepatotoxic Activitymentioning
confidence: 99%